Emerging therapeutic targets for sepsis. (4th March 2021) - Tindal, Elizabeth W.; Armstead, Brandon E.; Monaghan, Sean F.; Heffernan, Daithi S.; Ayala, Alfred
ABSTRACT: Introduction: Sepsis is characterized by a dysregulated host response to infection. Sepsis-associated morbidity/mortality demands concerted research efforts toward therapeutic interventions which are reliable, broadly effective, and etiologically based. More intensive and extensive investigations on alterations in cellular signaling pathways, gene targeting as a means of modifying the characteristic hyper and/or hypo-immune responses, prevention through optimization of the microbiome, and the molecular pathways underlying the septic immune response could improve outcomes.] Areas covered : The authors discuss key experimental mammalian models and clinical trials. They provide an evaluation of evolving therapeutics in sepsis and how they have built upon past and current treatments. Relevant literature was derived from a PubMed search spanning 1987–2020. Expert opinion : Given the complex nature of sepsis and the elicited immune response, it is not surprising that a single cure-all therapeutic intervention, which is capable of effectively and reliably improving patient outcomes has failed to emerge. Innovative approaches seek to address not only the disease process but modify underlying patient factors. A true improvement in sepsis-associated morbidity/mortality will require a combination of unique therapeutic modalities.